The translation of advertisements: issues of semiotics, symbolism and persuasion - Kappe, Christelle Fokam (My University, 2012)
This research report discusses the translation of advertisements paying attention to persuasion, semiotics, and symbolism. It illustrates the importance of symbolism and semiotics in persuading consumers across cultures. The research uses Coca‐Cola as a case study in order to discuss the strategies used by translators in translating persuasive text in print advertisements across cultures and to elaborate on key issues in the translation of advertisements and on theories that are very useful to translators of advertising materials. Semiotics, symbolism and the techniques used by advertisers and translators in persuading, as well as theories related to the translation of advertisements such as skopos theory, relevance theory and functional equivalence are discussed in the literature review and are assessed in the corpus analysis. The importance of sociology, culture and ideology is also illustrated in the study and a brief discussion of the discourse of advertisements is given in order to understand the mechanism of advertisement. This is because translators need to understand how advertising functions before they can translate it. This research report performs a comparative analysis of 30 Coca‐Cola advertisements in English and their translations into French from 1905 to 2011. By analysing and comparing the English advertisements of Coca‐Cola and their translations, this study shows how semiotics and symbolism may be used to analyse the techniques that are used in the advertisements to achieve persuasion in the different French settings. The analysis is further based on Relevance theory, Equivalence theory and skopos theory within the framework of DTS. Observations include translators’ understanding and good management of the visual and textual elements and good understanding of how to render an advertisement truly global by focussing on global, universal and neutral values.
M.A. University of the Witwatersrand, Faculty of Humanities (Translation), 2012